Histopathologic diagnosis of chronic viral hepatitis - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2016)
Morphological evaluation of the liver continues to play a central role for the diagnosis, grading and staging of chronic viral hepatitis. The defining morphology is necroinflammation, that is hepatocyte injury and inflammation. Hepatocyte injury is usually irreversible, and presents as apoptosis and/or necrosis. Mononuclear cell infiltration of the portal tracts, that is usually accompanied by periportal (interface) and lobular inflammation is typical. Continued necroinflammatory activity at the limiting plate destroying periportal parenchyma initiates fibrogenesis leading to cirrhosis. Fibrosis can be reversible with fragmentation of scar tissue, resolving vascular derangements and parenchymal regeneration. Grading is a measure of the intensity of necroinflammatory activity and staging is a measure of fibrosis and architectural alteration. Besides staging, Laennec scoring system, subdividing cirrhosis that is based on histologic parameters of fibrous septa width and number, has been advised to be used in reporting chronic viral hepatitis.
Keywords: Viral hepatitis; Grading; Staging; Biopsy